Pengaruh Rasio Likuiditas, Rasio Leverage, Dan “Rasio Profitabilitas Terhadap Return Saham Dengan Eps Sebagai Variabel Intervening Pada Perusahaan Manufaktur Tahun 2017-2019 - Pristy Indah Nurfiana; N. Rachma; Khalikussabir Khalikussabir (UNIVERSITAS ISLAM MALANG, 2021)
AbstractThis study aims to examine the effect of liquidity ratios, leverage ratios, and profitability ratios on returns stockwith EPS as an intervening variable. The population in this study are all manufacturing companies listed on the Indonesia Stock Exchange in 2017-2019. The research sample used purposive sampling technique. From a population of 179 companies, 27 companies were sampled with a three-year research period (2017-2019). The data analysis technique used is path analysis (path test). Based on the research results, it shows that ROE directly has a significant effect on EPS, while CR, DER, and ROA directly have no significant effect. Then DER, ROA, and ROE directly have a significant effect on returns stock, while CR directly has no significant effect on returns stock. Earning per share (EPS) directly has a significant effect on returns stock. CR, DER, and ROA indirectly have a significant effect on returns stockwith earnings per share (EPS) as an intervening variable. Meanwhile, return on equity (ROE) indirectly has no significant effect on returns stockwith EPS as an intervening variable. Keywords: liquidity ratio, leverage ratio, profitability ratio, stock returns, EPS